Priority conceptual problems of state regulation of operations in innovation sphere under modern russian conditions - O. N. Dmitriev; S. V. Novikov (Управление)
The criticality of innovation activity in relation to the sphere of high-tech national production in the current situation is argued. The existence of a systemic innovation crisis in modern Russia is stated with motivation. A number of causes of its occurrence, existence and aggravation - both internal and external are singled out. The sphere of formation and implementation of innovative operations in relation to the current conditions of the Russian economy with a predominant focus on high-tech industrial production is conceptually structured. Produced the delimitation of spheres direct the implementation of innovative operations of producers of novations (novators) and their customers (innovators), as well as the service sphere, highlighting donors returnable borrowing - primarily of banks, insurance companies, consulting agencies and maintain the appearance of the infosphere. The structural and functional analogies with the typical sphere of marketing operations are given. The typology of innovative operations on the basis of country-based deployment of novators and innovators is introduced. Shows the dominance of the objective of innovation through the channel of import and domestic innovation channel. The basic typology of regulatory operations of public administration in relation to innovation and investment is introduced. The sphere of organization of tenders for the execution of orders for the production of innovative products, integrated with the sphere of legislative and other regulatory regulation, is emphasized. The analysis of the existing basic regulations of normative legal regulation in this sphere and the derivatives generated problems taking into account the realities of the materialization of behavioral models of the typed operators of the innovation sphere is presented. A number of fundamental conceptual innovations in the field of this regulation, including those focused on the use of the activity potential of the subjects of innovation activity, are proposed.